Republic of Serbia : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2008)
The Serbian economy has continued to grow strongly, but external imbalances have widened along with vulnerabilities. To contain domestic demand, fiscal surpluses are needed, until the benefits of structural reforms are reaped. Low inflation should be entrenched by adoption of inflation targeting once government support and sound fiscal policies are in place. Competitiveness should be restored through corporate restructuring and wage moderation. Accelerating structural reforms is the key. Financial stability risks have been managed by building adequate buffers. The supervisory framework should continue to be strengthened.